2022
DOI: 10.1007/s40572-022-00359-3
|View full text |Cite
|
Sign up to set email alerts
|

What Is “Socioeconomic Position (SEP),” and How Might It Modify Air Pollution-Health Associations? Cohering Findings, Identifying Challenges, and Disentangling Effects of SEP and Race in US City Settings

Abstract: Purpose of Review Environmental epidemiology has long considered socioeconomic position (SEP) to be an important confounder of pollution effects on health, given that, in the USA, lower-income and minority communities are often disproportionately exposed to pollution. In recent decades, a growing literature has revealed that lower-SEP communities may also be more susceptible to pollution. Given the vast number of material and psychosocial stressors that vary by SEP, however, it is unclear which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…In general, regions that attained higher averages of particulate matter corresponded to areas with lower MHDI values (Fig. 3), aligning with previous studies (Clougherty et al, 2022;da Motta Singer et al, 2023).…”
Section: Spatial and Temporal Analysis Of Pm 25supporting
confidence: 91%
“…In general, regions that attained higher averages of particulate matter corresponded to areas with lower MHDI values (Fig. 3), aligning with previous studies (Clougherty et al, 2022;da Motta Singer et al, 2023).…”
Section: Spatial and Temporal Analysis Of Pm 25supporting
confidence: 91%
“…We found that associations of air pollution exposure with asthma were elevated among Black children and children born to mothers without a high school diploma. These results are consistent with prior studies showing that socioeconomic position (SEP) and race are key drivers of elevated environmental exposures, including air pollution, and race and SEP, each of which can be independently or synergistically associated with elevated physiologic stress leading to inflammation that increases susceptibility to disease, including asthma . In addition, Black children are more likely to be exposed to adverse childhood experiences, poor housing quality and indoor environments, and have less access to healthy food and greenspace .…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with prior studies showing that socioeconomic position (SEP) and race are key drivers of elevated environmental exposures, including air pollution, and race and SEP, each of which can be independently or synergistically associated with elevated physiologic stress leading to inflammation that increases susceptibility to disease, including asthma. 28 , 29 In addition, Black children are more likely to be exposed to adverse childhood experiences, poor housing quality and indoor environments, and have less access to healthy food and greenspace. 30 These factors, likely in combination, may inequitably affect Black children such that the negative health effects due to exposure to air pollution are heightened.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-economic position affects health via stress mechanisms and physical pathways (Clougherty et al 2022). At the same time, socio-cultural factors mediate the relation between actual pollution and risk perception .…”
Section: Insights From Indicator Studiesmentioning
confidence: 99%